Синтез і адсорбційні властивості кобальт-вуглецевого нанокомпозиту на основі лушпиння соняшнику - Bogatyrov, V. M.; Galaburda, M. V.; Oranska, O. I.; Borysenko, M. V.; Charmas, B.; Skubiszewska-Zięba, J.; Komar, M. A.; Voitko, I. I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2017)
Impregnation of sunflower seed husks with cobalt chloride with subsequent pyrolysis at 800 °C in an argon atmosphere allows obtaining metal-carbon magnetosensitive nanocomposites with developed microporosity. This method leads to formation of porous carbon and metal cobalt in cubic and hexagonal structural modifications, while a portion of cobalt forms a soluble compound in water. The size of cobalt crystallites of cubic modification was 20-21 nm, and hexagonal - 12-13 nm. The specific surface of the samples, depending on the synthesis conditions, ranged from 74 to 583 m2/g.